Effect of modified atmosphere packaging on the shelf life of chhana jalebi: A indian milk based confection - P, Geetha; R, Arivazhagan; M, Esther Magdalene Sharon (Indian Journal of Dairy Science, 2017)
Chhana jalebi is a traditional Indian milk product prepared by frying coils of batter made of chhana (acid coagulum of milk), starch and water, and soaking the fried coils in sugar syrup. The final product has a pleasant sweet taste and chewy body and texture. However, shelf life of chhana jalebi is low owing to several factors which affects its marketability.Â Enhancement of shelf life will give boost its market potential. Two methods were adopted for enhancing the shelf life of chhana jalebi viz. use of potassium sorbate (a class II permitted preservative) and modified atmosphere of nitrogen and carbon dioxide. Potassium sorbate was dissolved in soaking syrup at 800 pm concentration before the fried jalebi pieces were soaked in it. Modified atmospheres used were: 100% N2, 100% CO2 and a mixture of these gases (1:1) within metalized polyester packages. The color and appearance, flavor, body and texture and overall acceptability scores of the jalebi samples during storage at 28oC containing preservatives were recorded on 9-point hedonic scale and the scores were analyzed by ANOVA. It was observed from the results that as storage progressed the overall acceptability score decreased irrespective of the presence of preservative used or gases tried. However, potassium sorbate and modified atmospheres inside the package controlled the growth of microbes to increase the shelf life of the product up to 20-40 days at 28oC.